Control interno aplicado al proceso operativo del transporte de carga pesada en la empresa Transportes Unidos Especiales Asotusot (2023)
This article aims to show how the internal control applied to the operating process of the company Transportes Unidos Especiales “ASOTUSOT” is managed and how it is being affected. Once the document review has been carried out, it is intended to make known the influence of a good control system. internal control within this entity.